2018
DOI: 10.1111/cup.13132
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate cell histiocytosis in a Chinese patient with progressive and extensive nodular lesions and mixed indeterminate cell and macrophage‐monocyte lineage

Abstract: Indeterminate cell histiocytosis (ICH) is an extremely rare cutaneous neoplastic disorder. It has the immunophenotypic features of both Langerhans and non-Langerhans cell histiocytosis. We report here a case of a healthy young Chinese woman who presented with disfiguring, thick, infiltrated cutaneous nodules on the face, trunk and extremities which appeared progressively over a period of 4 years. No systemic involvement has been detected so far. Results of a skin biopsy showed diffuse dermal infiltration of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Chemotherapy must be used for aggressive cutaneous ICH, which involves over 50% of the body surface area and lasts for at least 6 months with no spontaneous resolution and new appearing lesions. There are four reports of ICH association with malignancies: one case of mast cell leukemia, another patient with myelomonocytic leukemia, and two cases with low grade B-cell lymphomas (8,14,18). Our case was not associated with hematologic malignancy, which was ruled out.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Chemotherapy must be used for aggressive cutaneous ICH, which involves over 50% of the body surface area and lasts for at least 6 months with no spontaneous resolution and new appearing lesions. There are four reports of ICH association with malignancies: one case of mast cell leukemia, another patient with myelomonocytic leukemia, and two cases with low grade B-cell lymphomas (8,14,18). Our case was not associated with hematologic malignancy, which was ruled out.…”
Section: Discussionmentioning
confidence: 56%
“…Birbeck granules that characterize Langerhans cells cannot be detected by electron microscopy in ICH histiocytes. Nowadays, it is proposed that ICH could be a non-Langerhans' cell histiocytosis variant, but its pathogenesis has remained unknown (5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We then selected and included in the study 78 papers, describing 108 patients (Figure 1). 5,8,9,12,32–106 From two case series, we included only some of the described patients, as indicated in Table 1 12,48 …”
Section: Resultsmentioning
confidence: 99%
“…Of those 10 cases, 5 demonstrated ETV3-NCOA2 gene fusion (Table 1). 3–7 Brown et al 3 (2015) also demonstrated that FISH for ETV3-NCOA2 translocation was negative in a group of patients without ICH, which included patients with Langerhans cell histiocytosis or non-Langerhans cell histiocytoses. These studies together suggest that ETV3-NCOA2 gene fusion may be a specific but nonsensitive marker for ICH.…”
Section: Discussionmentioning
confidence: 99%